Le système scolaire face à l’instruction dans la famille - Alain Quatrevaux (Cahiers de la Recherche sur l'Education et les Savoirs)
The analysis of reports of inspections carried out by French national education permits an approach to a theme that is barely visible in France, that of “homeschooling”, and especially reveals the scholastic-centricity which is characteristic of the French education system. This system does not bring itself to admit, despite the existence of laws and decrees on the subject, that an education outside school can be anything other than a last resort, applicable to certain marginal cases. The analysis thus describes the procedures which tend to justify, legitimate, or even impose the sole scholastic institution on those who decide to educate their children themselves and who are subject to random and often inappropriate testing. The case of these families who oppose (or at least are perceived to oppose) de facto the monopolistic norm of the school system poses the whole problem of suspicion against all educational forms other than that of official school education.